Students’ Difficulties in Speaking at Universitas Pasir Pengaraian - Rahayu, Pipit; Eripuddin; Syafitri, Fivi; Kasyulita, Evi (Proceeding of International Conference on Language Pedagogy (ICOLP), 2021)
The purpose of this research was to find out the difficulty in speaking at Universitas Pasir Pengaraian. The researcher found students have difficulty in speaking because their lack of vocabulary rarely to practice speaking and they got nervous in speaking because of lack of ability. The methodology of this research was descriptive qualitative. The samples were 29 students. In collecting the data, the researcher used questionnaire and interview. The result of questionnaire and interview showed that most of the students often did a grammatical errors in speaking, often think in their mother tongue when speaking, they had difficulty leading class discussion in English, and they also felt nervous when they speak English. Students also felt they lack of opportunities to speak English outside the class and sometimes feel difficulty in giving speeches in English in front of the whole class. Meanwhile, the external factors that dominated their difficulties in speaking were their parents did not support the, their neighborhood could not help them to improve their speaking ability, they had no friends to practice speaking, and people around them could not help them to improve their speaking ability. In the short, it can be seen that most students difficulties in speaking.